Usabilidade na recuperação da informação: um enfoque no catálogo Athena - Banhos, Vângela Tatiana Madalena [UNESP] (2008)
The research conducts a study about a specific catalog, the Athena, considered a system of retrieval of information structured and organized. In this environment you have to evaluate a set of guidelines for usability and apply them in systems for retrieval of information on the Web, taking into account aspects relating not only to the usability of its interface, but also its efficiency in the recovery process. The study is characterized as exploratory and descriptive and analytical. Thus, it was initially to review the national and international literature on recovery of information and usability in various informational sources, printed and electronic, as the theoretical work. In the second stage, was a heuristic analysis, and finally usability tests were carried out with users that were applied in two procedures: a semi-structured questionnaire and an instrument of observation. After the analysis of quantitative and qualitative data, the test allows users to determine how they interact with the interface of the Athena Catalog and the forms of search that usually take place in other tools available on the Web was also possible to validate some notes made in heuristic analysis, because the majority of the research has shown to have no experience in the use of Athena Catalog. This research shows the importance of applying the tests with users in environments of retrieval of information, considering them a vital part in the development of any system.